Implementation of Brain Gym Habits for Children at Tirtayasa Islamic Kindergarten - Wardhani, Dina Kusuma; Hidayati; Jannah, Roihatul; Putri, Melani Duwita; Patrisia, Rezza Aini Patrisia; Nurasiah, Aas; Apriyani, Ria Bela Apriyani; Rismawati, Gita Triana; Sulistianti, Nadia Melita; Rahmawati, Sintia (Contemporary Journal of Applied Sciences, 2024)
Brain gymnasium is related to the ability to integrate the upper brain (cortex) and lower brain (brainstem), and the lateral and focus dimensions are related to the ability to integrate the back and front of the brain. Early childhood development learning patterns can be improved by combining the left and right brain. This study uses a qualitative descriptive approach. Data were collected through observation, interviews, and documentation. Interviews were conducted with the principal and class teachers and documentation was collected of several activities carried out by the children of Tk Islam Tirtayasa brain gym before the start of learning taking place in their respective classes for example Brain buttons (brain switch), The thinking cap (plug your ears), Brain cross crow (cross movement), Brain lazy 8s (sleeping eights), Hook Ups (relaxing hooks) and Uniting the brain because it becomes easier and more focused